2022
DOI: 10.1007/s10123-022-00290-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal activity of human antimicrobial peptides and their synergistic interaction with common antifungals against multidrug-resistant Candida auris

Abstract: Emergence of Candida auris, a multidrug resistant yeast, demonstrates the urgent need for novel antifungal agents. Human antimicrobial peptides (AMP) are naturally occurring molecules with wide spectrum antimicrobial activity, particularly against a variety of fungi. Therefore, this study examined the antifungal activity of seven different human AMPs against C. auris following the CLSI guidelines. The antifungal activity was further assessed using time kill curve and cell viability assays. For combination inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Considering this, AMPs have been suggested as the most promising candidates for combating antifungal resistance [28]. Previously, we have shown that particular human AMPs exhibited fungicidal activity against C. auris and altered its membrane permeability as a mechanism of action [19]. Several studies, however, have revealed that many AMPs with membrane-interacting effects exhibit additional mechanisms such as induction of apoptosis [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering this, AMPs have been suggested as the most promising candidates for combating antifungal resistance [28]. Previously, we have shown that particular human AMPs exhibited fungicidal activity against C. auris and altered its membrane permeability as a mechanism of action [19]. Several studies, however, have revealed that many AMPs with membrane-interacting effects exhibit additional mechanisms such as induction of apoptosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 illustrates the MIC and MFC results for peptides and antifungals against two C. auris isolates, which were determined in this research and in prior study [19]. The antifungals (fluconazole, amphotericin B and caspofungin) were initially used to further confirm the susceptibility pattern of the tested strains and determine test concentration for further experiments.…”
Section: Susceptibility Testing For Peptides and Antifungalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human body is also a potent source of antifungal peptides, so far many peptides with different biological functions were reported from the human body. Peptides like human β-defensin-3 [72], human cathelicidin peptides LL-37 [73] and salivary histatin-5 [74] were recently reported with antifungal activity on C. auris (Table 3). Human β-defensin-3 and cathelicidin peptides LL-37 produced 100% and 70% of synergy with fluconazole [72,73].…”
Section: Peptide-based Strategies For Eradicating C Aurismentioning
confidence: 99%
“…They exhibit broad-ranging antimicrobial activity and are particularly effective against many strains of fungi. Several research efforts have focused on investigating the synergistic combination of these peptides with commercial antifungals, with the aim of creating new therapeutic agents that not only increase efficacy but also decrease the occurrence of adverse effects [ 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%